Anterior Minithoracotomy vs. Transcatheter Closure of Patent Ductus Arteriosus in Very Preterm Infants - Lenoir, Marien; Wanert, Chloé; Bonnet, Damien; Méot, Mathilde; Tosello, Barthélémy; Fouilloux, Virginie; Ovaert, Caroline; Malekzadeh-Milani, Sophie (Frontiers in Pediatrics, 2021)
Introduction: Patent ductus arteriosus (PDA) is common in preterm infants and contributes to morbidity and mortality. Several studies have shown the feasibility and safety of percutaneous PDA closure. Minimally invasive surgical ligation by anterior thoracotomy is an alternative, bedside technique for PDA closure in very low birth weight preterm infants. Our study aimed to compare short- and medium-term morbidity and mortality between anterior minithoracotomy and transcatheter PDA closure. Methods: From 2010 to 2020, 92 preterm infants <1,600 g underwent PDA closure in two centers: 44 surgical anterior minithoracotomies (center 1) and 48 transcatheter closures (center 2). Using a 1:1 propensity score match analysis, 22 patients in each group were included. The primary outcome was time to extubation after intervention. Results: Preoperative characteristics were similar in both groups after propensity matching (mean weight at procedure, 1,171 ± 183 g; p = 0.8). Mean time to extubation was similar: 10 ± 15 days in the surgical group vs. 9 ± 13 days in the transcatheter group (p = 0.9). Mean age at hospital discharge was 114 ± 29 days vs. 105 ± 19 days (p = 0.2). Two deaths occurred in the surgical group and one in the transcatheter group (p = 0.61). Five complications (pneumothorax n = 2, chylothorax n = 2, phrenic nerve injury n = 1) occurred in three patients after surgery. Three complications (chylothorax n = 1, endocarditis n = 1, renal vein thrombosis n = 1) occurred in two patients after percutaneous closure (p = 0.63). Conclusion: Equivalent efficiency and safety of surgical mini-invasive vs. transcatheter PDA closure in preterm infants <1,600 g are in favor of applying these alternative techniques according to centers' facilities and competences.